Job satisfaction : a predictor of working efficiency and intentions to remain in nursing - Ajhenberger, Sajma (Array, 2020)
Introduction. We consider job satisfaction through the prism of the work we do, the working conditions, the relationships with colleagues and superiors, and the opportunity to advance and earn. Nurses make up 50% of the total workforce in the healthcare system and it is beyond question that their number in the system directly affects the quality of nursing care. The most common dissatisfaction at work is insufficient staff, poor working conditions, poor relationship with colleagues and superiors, and impossibility to advance. Aim. The objectives of the study were to examine the satisfaction of nurses in the job and to assess whether they were considering leaving their current job and how they were assessing their health and working productivity. Methods. The study involved 155 nurses from three Clinical Hospital Centers in Croatia (Osijek, Rijeka and Zagreb). The study was designed as a cross-sectional study. It started on January 1, and ended on June 30, 2018. The first part refers to the demographic dana of the respondents, while the second part contains questions related to the intention of leaving the present job, self-assessment of health status and working productivity and job satisfaction. Results. In the answers to job satisfaction claims, the respondents with the bachelor’s and master’s degree in nursing compared to the respondents who completed secondary education, responded with a higher percentage that they were dissatisfied with the working conditions and the possibility of promotion (46.2%). They are dissatisfied with the relationship with their superiors (70%), as well as with the work they do (54%). Respondents at all levels of education are equally satisfied with their relationships with colleagues and with their earnings. Conclusion. Most of the respondents are satisfied with the relationship with their superiors, colleagues and work, and dissatisfied with the possibility of advancement and salary.